(untitled) (Scientific journal of the Fergana State University, 2025)
Abstract Reflexive culture, as an integral part of the modern professional education system, forms in students not only the ability to improve their knowledge but also the ability to deeply analyze their actions in professional activities. This article examines the theoretical foundations of developing the reflexive culture of future doctors in the educational process at medical universities. Reflexive culture plays an important role in students’ professional growth, self-analysis, and effective patient care. The development of this culture requires teachers to integrate a reflective approach into the educational process. Analyzing pedagogical methods, the article proposes strategies for the formation and development of reflective thinking that meets the needs of modern vocational education. Analyzing pedagogical methods, the article proposes strategies for the formation and development of reflective thinking that meets the needs of modern vocational education. This means that the inclusion of the proposed methods in the curriculum of medical higher educational institutions will be effective in improving the quality of education for future doctors.